School Reforms in Ontario: The "Marketization of Education" and the Resulting Silence on Equity - Sefa Dei, George J.; Karumanchery, Leeno L. (Alberta Journal of Educational Research, 1999)
Market dynamics have begun to entrench themselves in educational systems around the world. Although this phenomenon has been addressed in several recent writings (Ball, 1993; Dehli, 1996; Gerwitz, Ball, & Bowe, 1995; Kenway, 1993; Robertson, 1995), few have incorporated a critical antiracist framework. As noted by Dehli (1996) the encroachment of market forms, relations, and concepts into educational sites usually results in the marginalization and muting of other dimensions of schooling. Using an integrative antiracist perspective that is informed by the findings of an ongoing study of inclusive schooling in Ontario (Dei et al, 1996), this article critically examines these ongoing reforms in a Canadian context, specifically in relation to the recent reforms in Ontario's educational system. We draw on knowledge about race and difference to argue for serious questioning of these reforms and their impact on socially disadvantaged groups. In doing so, the article asserts that current trends are leading toward the " Marketisation of education" (Ball, 1993; Gerwitz et al., 1995; Kenway, 1993) in Ontario, and that the harmful consequences of this shift will be felt most severely in relation to issues of equity and access in education. Through the rhetoric of cost-effectiveness and bureaucratic efficiency, the "official" agenda for educational change shifts focus away from equity considerations in schooling to those of capital, market forces, and big business. The article interrogates the rhetoric of reform and calls for equity to be placed at the centre of educational change. In conclusion we suggest new ways of examining and addressing genuine educational options in Canadian contexts.